PERANCANGAN SISTEM INFORMASI BERBASIS WEB UNTUK PENGENALAN DAN PENDATAAN B2SA (BERAGAM, BERGIZI, SEIMBANG, DAN AMAN) - Pratiwi; S. Pasaribu , Johni (INFOKOM (Informatika & Komputer), 2026)
The implementation of the Diverse, Nutritious, Balanced, and Safe (B2SA) dietary pattern is essential to improve the nutritional status of the Indonesian community. However, nutritional literacy remains low, especially among adolescents, thus requiring an effective and accessible educational medium. This study aims to design and develop a web-based information system called SIBASA (B2SA Information System) as a platform for nutritional education and community food consumption data collection. The application provides B2SA educational content, meal portion data based on age, nutritional information, and an interactive dashboard for visualizing nutritional data. The system was developed using the Waterfall method and a Model-View-Controller (MVC) architecture. System testing indicated that all application features functioned well, were responsive across devices, and effectively delivered educational content and nutritional data. Therefore, SIBASA is considered feasible as a digital educational medium and a web-based tool for nutritional data management with potential for further development.